Do corpo na prisão à prisão no corpo: tornozeleiras eletrônicas e direitos humanos na literatura científica brasileira - Silva, Ana Rafaella Vieira Fernandes (2022)
Electronic anklets were inserted into the Brazilian legal system in 2010, supported, among other arguments, by the narrative that they would be more “humanitarian” punitive instruments compared to prison and that they would contribute to the reduction of the prison population, the reduction of expenses of prisons and the rehabilitation of convicts, in a context of collapse of the Brazilian prison system. However, data from the National Penitentiary Department on the Brazilian prison system (BRAZIL, 2022) demonstrate that there were no significant impacts on the announced objectives, making it necessary to investigate the real effects of adopting this instrument in Brazilian criminal policy, especially on people subjected to the penal system. This dissertation has the general objective of analyzing, through a systematic literature review, the Brazilian scientific production regarding the use of electronic anklets in the period from 2010 to 2021, to problematize how the debate on human rights has appeared in studies. In searches in the databases Portal de Periódicos da CAPES, PEPSIC, BVS, Scopus Preview, SciELO and Google Scholar, 49 articles considered relevant for this study were obtained. A significant prevalence of qualitative research with bibliographic and/or documentary procedures was identified (38 articles) to the detriment of field research (11 articles). Among the field surveys, only 6 conducted interviews with monitored subjects. After a thorough reading of the materials, five theoretical categories were created, with a view to exploring and problematizing the discussions presented in the articles in light of the theoretical articulation between Critical Criminology and Human Rights: a) Human dignity and fundamental rights and guarantees; b) Social control through the penal system; c) Resocialization; d) Gender issues; and e) What emerges despite the lack: the monitored subjects' perception of anklets. The analysis reveals that concepts such as “human dignity”, “humanization” and “human rights”, as well as “efficacy”, “utility” and “resocialization”, are abstractly invoked to legitimize the social control undertaken by electronic anklets, while its effects on the lives and rights of people selected by the punitive system are often disregarded in debates on the aforementioned criminal public policy. It is argued that the dignity of the human person and human rights need to break the merely discursive and rhetorical sphere and produce concrete effects in the lives of people subjected to the penal system. It is concluded that ankle bracelets produce human rights violations, violence and stigmatization that do not represent any humanization of punishment, and that they have operated as effective instruments for the expansion and technological updating of penal control in the capitalist system. Furthermore, it is suggested a greater production of research aimed at listening to the monitored people so that their experiences contribute to the scientific production on the Brazilian electronic monitoring policy, enabling the construction of academic knowledge committed to the realization of human rights.